Ameliorative Effects of Raisin Polyphenol Extract on Oxidative Stress and Aging In Vitro and In Vivo via Regulation of Sirt1–Nrf2 Signaling Pathway - Wenjing Gao; Caiyun Zhao; Xin Shang; Bin Li; Jintian Guo; Jingteng Wang; Bin Wu; Yinghua Fu (Foods)
Raisins are an important source of polyphenolic compounds in plant foods, and polyphenols are associated with antioxidant and anti-aging activity. In this work, 628 polyphenols in raisin extracts were characterized using UPLC-MS/MS, mainly including tricetin 3′-glucuronide, diisobutyl phthalate, butyl isobutyl phthalate, isoquercitrin and 6-hydroxykaempferol-7-O-glucoside. The oxidative stress in H2O2-induced HepG2 cells and D-gal-induced aging mice was alleviated by raisin polyphenols (RPs) via increases in the cellular levels of superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH), along with decreases in malonaldehyde (MDA), reactive oxygen species (ROS) and advanced glycosylation end-products (AGEs) levels. In addition, it was observed that RPs enhanced Sirt1 and Sirt3 expression, initiating the Keap1-Nrf2 signaling pathway, by upregulating the levels of nuclear Nrf2, facilitating the expressions of the antioxidant proteins NQO1 and HO-1, and downregulating Keap1 and cytoplasmic Nrf2 protein levels in H2O2-induced HepG2 cells and D-gal-induced aging mice. In summary, RP exerted antioxidant and anti-aging effects via regulating the Sirt1–Nrf2 signaling pathway in vitro and in vivo.